Comparative Anatomical Study of Keel in Chicken and Duck - Hamid, Asadullah (Journal of Natural Sciences – Kabul University)
The skeletons of fowl, including chickens and ducks, are compact and pneumatized. The developmental stages of the keel bone in fowl progress slowly, and its ossification takes a considerable amount of time. The keel is the largest bone in the fowl skeleton, and its development is particularly pronounced. This study conducts a comparative anatomical analysis of the keel in ducks and chickens. In this research, the keel bone was measured using a ruler and tape. The results show that the keel bone in male ducks and cocks is larger than that of females. Additionally, the keel in both male and female ducks is wider than in chickens. This wider keel in ducks may be attributed to their living habits and swimming behavior.